Trialling one-part geopolymer production including iron ore tailings as fillers. Issue 5 (28th May 2022) - Mazzinghy, Douglas B.; Figueiredo, Ricardo A.M.; Parbhakar-Fox, Anita; Yahyaei, Mohsen; Vaughan, James; Powell, Malcolm S.
ABSTRACT: Mining is facing a transformation in terms of environmental and social performance with improved mine waste management practices required. The valorisation of iron ore tailings, a fine material rich in silica, should be sought as it can be used in geopolymers. In this study a methodology to produce a one-part geopolymer using iron ore tailings as fillers is presented. All experiments used 50 wt.% of tailings with varying proportions of activators tested. The best result of compressive strength achieved is 48.1MPa after 28 days curing at room temperature. This study demonstrates the potential application for using geopolymers as future construction materials.